Multi-skilling at a provincial training centre institution : post training evaluation - Florence, Taryn Merillia (Cape Peninsula University of Technology, 2011)
As global and national markets become more competitive, businesses are forced to become more adaptable and the public service is by no means exempt from this phenomenon. Owing to a dynamic and ever-changing work environment, it is necessary for public servant employees to continuously update their knowledge and skills. However, in most organisations, the impact of training and development programmes are undermined. The value placed on increasing knowledge and skills is limited to attending a training programme. As a result, the newly acquired information and competencies are very seldom transferred from the classroom to the workplace and without a definite increase in performance and in service delivery; the contribution of actual learning is questionable. This research study therefore uses the Integrated Integrated Human Resource Administration and Persal (IHRAP) Programme (presented by the Western Cape Provincial Training Institute) to gauge the importance of post training evaluation and the benefits that can be derived from it, both for the department and the employee. In addition, the study evaluates whether the participants of the training programme are able to apply concepts and techniques learned in the classroom. It focuses specifically on human resource employees employed within the Provincial Government of the Western Cape, who is responsible for performing a number of different human resource functions. A survey was conducted amongst the participants of the IHRAP programme using a research questionnaire. After the results of the survey were collected and analysed, the researcher was able to determine where there were gaps in the post training evaluation process. Several recommendations are made to bridge these gaps and in doing so, enable the training programme to have a greater impact on the participants and in the workplace. In addition to evaluating the IHRAP programme, the need for continuous improvement in skills will always be essential, but departments must create the opportunities for participants to exercise these acquired skills effectively.
Thesis (MTech (Human Resource Management))--Cape Peninsula University of Technology, 2011
Keywords: Employees -- Training of -- South Africa; Occupational training -- South Africa; Skilled labor -- Training of -- South Africa; Mentoring -- Personnel management -- South Africa; Multi-skilling; Intergrated Human Resource Administration and Persal (IHRAP) Programme